Towards an enterprise architecture for healthcare system and information technology: state of the art and future trends - Zainuddin, Ahmad Anwar; Chung, Chun Kit; Mat Rosani, Aiman Najmi; Abdul Rahman, Siti Husna; Kamarudin, Saidatul Izyanie; Ahmad Puzi, Asmarani; Subramaniam, Krishnan (Springer Nature, 2024)
Enterprise architecture (EA) integrates and develops organisational components for strategic planning. It helps define IT component linkages and engage paramedical workers in healthcare. It also creates the greatest healthcare enterprise architectural framework. Commonly, the senior management must grasp enterprise architecture to choose a business-IT- aligned organisation. The study examines healthcare organisations' EA adoption issues before, during, and after. To fix these difficulties and streamline the process. The report recommends healthcare EA implementation. To improve implementation, these principles streamline processes, stimulate collaboration, and improve patient outcomes. EA boosts healthcare performance, but IT-human interaction must be reviewed. The healthcare businesses must overcome challenges to deploy smoothly and achieve great results.